The present vaccinoprophilaxis of tick-borne encephalitis and vaccines for its provision - M. S. Vorob’Eva; M. N. Rashchepkina; L. I. Pavlova; L. D. Bystritsky; N. H. Stavitskaya; T. E. Iltchenko; G. P. Bilalova; I. A. Mishchenko; O. I. Sharova (Бюллетень сибирской медицины)
The high rate of tick-borne encephalitis (TBE) morbidity is lasting for recent years in many areas of Russian Federation. Vac- cination with TBE vaccine is considered to be most effective mean of TBE prophylaxis in endemic areas. VIRION branch (in Tomsk) of MICROGEN State Company have been producing inactivated TBE vaccines for more than 40 years. Since 2001 VIRION have been producing and selling novel purified concentrated TBE vaccine EnceVir. Vaccine EnceVir contains inactivated TBE virus of Far Eastern subtype as active substance with high level of its purity. The vaccine substantiated high level of immuno- genicy and safety in adult and children clinical trials. Postmarketing surveillance during 2001—2005 has verified these conclusions. Hence EnceVir is effective, safe and most available regarding value vaccine for mass vaccination campaign in Russian Federation.